2005
DOI: 10.1002/mnfr.200500008
|View full text |Cite
|
Sign up to set email alerts
|

Assay of advanced glycation endproducts in selected beverages and food by liquid chromatography with tandem mass spectrometric detection

Abstract: Food and beverages contain protein glycation adducts--both early-stage adducts and advanced glycation endproducts. We determined the concentrations of glycation adducts in selected food and beverages by liquid chromatography with triple quadrupole mass spectrometric detection. Cola drink contained low concentrations of glycation free adducts, whereas pasteurised and sterilised milk were rich sources of heat-stable glycation adduct residues--Nepsilon-carboxymethyl-lysine and Nepsilon-carboxyethyl-lysine. Labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
115
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 147 publications
(126 citation statements)
references
References 36 publications
6
115
1
Order By: Relevance
“…Glyceraldehyde, which could be derived from glucose metabolism, is not a major sugar in vivo and its incubation with proteins will generate a large number of AGEs; in addition, there is some criticism that measurement of AGEs using liquid chromatography-tandem mass spectrometry technique may produce different results to that using ELISA (129). However, our series of studies have suggested that serum levels of glyceraldehyde-derived AGEs might be a novel biomarker for insulin resistance and vascular injury and may predict future cardiovascular events in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Glyceraldehyde, which could be derived from glucose metabolism, is not a major sugar in vivo and its incubation with proteins will generate a large number of AGEs; in addition, there is some criticism that measurement of AGEs using liquid chromatography-tandem mass spectrometry technique may produce different results to that using ELISA (129). However, our series of studies have suggested that serum levels of glyceraldehyde-derived AGEs might be a novel biomarker for insulin resistance and vascular injury and may predict future cardiovascular events in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of AGE fluorescence capacity is simple but nonspecific. Specific AGE can be identified and quantified by ELISA, HPLC, or mass spectrometry (26). …”
Section: Age Are Metabolic Mediators Of Kidney Damagementioning
confidence: 99%
“…4E). To assess the whole-body formation of MG-H1, we measured the urinary excretion of MG-H1 free adduct, corrected for MG-H1 absorbed from food by extrapolating regression of urinary MG-H1 on urinary pyrraline in all subjects to zero pyrraline (and hence no contribution from food) (25,26) (Fig. 4F).…”
mentioning
confidence: 99%